Les enfants du paradis [videorecording (DVD)] = Children of paradise - Carné, Marcel; Arletty, 1898-1992; Barrault, Jean-Louis, 1910-1994; Brasseur, Pierre, 1905-1972 (Criterion collection, 2002)
Drama about the theater and the individuals that made the stage their life. Includes the love story of four men for one woman.